Deptor is a novel target of Wnt/β-catenin/c-Myc and contributes to colorectal cancer cell growth - Wang, Qingding (Cancer Res, 2018)
Activation of the Wnt/β-catenin signaling pathway drives colorectal cancer (CRC) growth by deregulating expression of downstream target genes including the c-Myc proto-oncogene. The critical targets that mediate the functions of oncogenic c-Myc in CRC have yet to be fully elucidated. Previously, we showed that activation of PI3K/Akt/mTOR contributes to CRC growth and metastasis. Here we show that Deptor, a suppressor of mTOR, is a direct target of Wnt/β-catenin/c-Myc signaling in CRC cells. Inhibition of Wnt/β-catenin or knockdown of c-Myc decreased, while activation of Wnt/β-catenin or overexpression of c-Myc increased, the expression of Deptor. c-Myc bound the promoter of Deptor and transcriptionally regulated Deptor expression. Inhibition of Wnt/β-catenin/c-Myc signaling increased mTOR activation, and the combination of Wnt and Akt/mTOR inhibitors enhanced inhibition of CRC cell growth in vitro and in vivo. Deptor expression was increased in CRC cells; knockdown of Deptor induced differentiation, decreased expression of B lymphoma Mo-MLV insertion region 1 (Bmi1), and decreased proliferation in CRC cell lines and primary human CRC cells. Importantly, our work identifies Deptor as a downstream target of the Wnt/β-catenin/c-Myc signaling pathway, acting as a tumor promoter in CRC cells. Moreover, we provide a molecular basis for the synergistic combination of Wnt and mTOR inhibitors in treating CRC with elevated c-Myc.